2016
DOI: 10.1007/s11195-016-9428-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Symptoms Related to Hemodialysis Affect Marital Adjustment?

Abstract: All the symptoms experienced by patients undergoing hemodialysis (HD) impair their social lives including family relationships and marital adjustment. The purpose of this descriptive study is to determine the effect of HD symptoms on marital adjustment. The study included 282 voluntary patients who were aged 18 or over and were receiving HD treatment for at least 6 months. The data were collected by using a Patient Information Form, Dialysis Symptom Index (DSI), and Revised Dyadic Adjustment Scale (RDAS) throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
6
0
3
Order By: Relevance
“…It was found that dialysis patients need help at various levels while performing their daily life needs such as moving, shopping, participating in social activities, cooking, excretion, nutrition [30]. Göris found that HD treatment and its symptoms affect patients' family relationships and social lives negatively, including marital adjustment [19]. Sexual dysfunction is a common problem in CRF patients [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that dialysis patients need help at various levels while performing their daily life needs such as moving, shopping, participating in social activities, cooking, excretion, nutrition [30]. Göris found that HD treatment and its symptoms affect patients' family relationships and social lives negatively, including marital adjustment [19]. Sexual dysfunction is a common problem in CRF patients [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that sexual disorders have negative effects on self-esteem in interpersonal relations [31,33]. In the studies conducted, it was found that the symptoms experienced negatively affect the quality of life of the patients, their work, marriage and family relations [7,14,19]. As can be seen from our research findings and literature studies, individuals who receive HD treatment experience many hemodialysis symptoms that negatively affect their daily life activities, make life difficult, make themselves dependent on someone else, and affect their comfort.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu form, literatür incelenerek (18,20,21,24,25) araştırmacılar tarafından hazırlanmıştır. Sosyodemografik özellikler bilgi formu; hemodiyaliz hastalarının tanıtıcı özelliklerini içeren on soru ve hastalık özgeçmişleri ile ilgili altı sorudan oluşmaktadır.…”
Section: Tanıtıcı Bilgi Formuunclassified
“…Buna ek olarak, hemodiyaliz hastaları tarafından en sık deneyimlenen semptomlar arasında yorgunluk, ağrı, kas krampları, bulantı, kusma, konstipasyon, diyare, kaşıntı, deride kuruluk, uyku bozuklukları, emosyonel ve cinsel sorunlar yer almaktadır (15)(16)(17). Bu semptomların sıklığı ve şiddeti her hastada bireysel farklılıklar göstermektedir (15,(18)(19)(20)(21)(22).…”
Section: Introductionunclassified